Natural hybridization patterns between widespread Calanthe discolor (Orchidaceae) and insular Calanthe izu-insularis on the oceanic Izu Islands. (10th July 2019) - Nakahama, Naoyuki; Suetsugu, Kenji; Ito, Azusa; Hino, Masayuki; Yukawa, Tomohisa; Isagi, Yuji
Abstract: Natural hybridization often occurs between insular and widespread species, and investigating these hybridization patterns is important in improving our understanding of the evolution of insular plant species. To this end, we studied the floral morphology and genetic structure of the widespread species Calanthe discolor, the insular closely related species C. izu-insularis and their putative natural hybrids on Honshu Island (mainland) and the Izu Islands (oceanic islands), Japan, using microsatellite markers. Natural hybridization probably occurred on all the investigated Izu Islands in Japan, although C. izu-insularis was morphologically and genetically different from C. discolor . Bumblebees and other relatively large bees are not distributed in the Izu Islands and therefore natural hybridization would have occurred via pollination by relatively small solitary bees that are pollinators of both Calanthe spp. We also showed that in the islands more remote from the mainland, the proportions of insular C. izu-insularis increased and the floral morphologies of both species changed. The results suggested that insular C. izu-insularis evolved on the Izu Islands and the widespread C. discolor adapted to the poor pollinator fauna on oceanic islands.